Phytoplankton Phenology in the North Atlantic: Insights From Profiling Float Measurements - Yang, Bo; Boss, Emmanuel S.; Haëntjens, Nils; Long, Matthew C.; Behrenfeld, Michael J.; Eveleth, Rachel; Doney, Scott C. (Frontiers in Marine Science, 2020)
Phytoplankton division rate (µ), loss rate (l), and specific accumulation rate (r) were calculated using Chlorophyll-a (Chl) and phytoplankton carbon (Cphyto) derived from bio-optical measurements on 12 Argo profiling floats in a north-south section of the western North Atlantic Ocean (40° N to 60° N). The float results were used to quantify the seasonal phytoplankton phenology and bloom dynamics for the region. Latitudinally varying phytoplankton dynamics were observed. In the north, the CPhyto peak was higher, occurred later, and was accompanied by higher total annual CPhyto accumulation. In contrast, in the south, stronger μ-r decoupling occurred despite smaller seasonal variations in mixed layer depth (suggesting the possibility of other ecological forcing), and was accompanied by an increasing portion of winter to total annual production, consistent with relief of nutrient limitation. The float observations of phytoplankton phenology for the mixed layer were compared to ocean color satellite remote sensing observations and found to be similar. A similar comparison to an eddy-resolving ocean simulation found the model only reproduced some of aspects of the observed phytoplankton phenology, indicating possible biases in the simulated physical forcing, turbulent dynamics, and bio-physical interactions. In addition to seasonal patterns in the mixed layer, the float measurements provided information on the vertical distribution of physical and biogeochemical quantities and therefore are complementary to the remote sensing measurements. Seasonal phenology patterns arise from interactions between “bottom-up” (e.g., resources for growth) and “top-down” (e.g., grazing, mortality) factors that involve both biological and physical drivers. The Argo float data are consistent with the disturbance recovery hypothesis over the full, annual seasonal cycle; for the late winter/early spring transition, the float data are also consistent with other bloom hypotheses (e.g. critical photosynthesis, critical division rate, and meso/sub-mesoscale physics) that highlight the importance of brief, episodic boundary layer shoaling for decoupling of division and grazing rates.